Ectopic expression of the AtCDF1 transcription factor in potato enhances tuber starch and amino acid contents and yield under open field conditions - Carrillo, Laura; Baroja-Fernández, Edurne; Renau-Morata, Begoña; Muñoz, Francisco J.; Canales, Javier; Ciordia, Sergio; Yang, Lu; Sánchez-López, Ángela María; Nebauer, Sergio G.; Ceballos, Mar G.; Vicente-Carbajosa, Jesús; Molina, Rosa V.; et al. (Frontiers in Plant Science, 2023)
Cycling Dof transcription factors (CDFs) have been involved in different aspects of plant growth and development. In Arabidopsis and tomato, one member of this family (CDF1) has recently been associated with the regulation of primary metabolism and abiotic stress responses, but their roles in crop production under open field conditions remain unknown. In this study, we compared the growth, and tuber yield and composition of plants ectopically expressing the CDF1 gene from Arabidopsis under the control of the 35S promoter with wild-type (WT) potato plants cultured in growth chamber and open field conditions. In growth chambers, the 35S::AtCDF1 plants showed a greater tuber yield than the WT by increasing the biomass partition for tuber development. Under field conditions, the ectopic expression of CDF1 also promoted the sink strength of the tubers, since 35S::AtCDF1 plants exhibited significant increases in tuber size and weight resulting in higher tuber yield. A metabolomic analysis revealed that tubers of 35S::AtCDF1 plants cultured under open field conditions accumulated higher levels of glucose, starch and amino acids than WT tubers. A comparative proteomic analysis of tubers of 35S::AtCDF1 and WT plants cultured under open field conditions revealed that these changes can be accounted for changes in the expression of proteins involved in energy production and different aspects of C and N metabolism. The results from this study advance our collective understanding of the role of CDFs and are of great interest for the purposes of improving the yield and breeding of crop plants.